Determinants Creative MSMEs Financial Literacy In The Special Region Of Yogyakarta And Effect Of Competitive Advantage - Siti Resmi; Reza Widhar Pahlevi; Fran Sayekti (Journal of International Conference Proceedings (JICP), 2019)
Financial Literacy is knowledge about financial management that is owned in order to develop for a more prosperous life in the future. The urgency of financial literacy is to make education efforts in the financial sector to the people of Indonesia in order to be able to manage finances intelligently. Good financial literacy can produce good financial reports so that financial information can be accessed quickly and easily. Furthermore, it can be used for more accurate decision making and as a basis for winning competition. The good and poor level of financial understanding is influenced by recent education and gender. The phenomenon that occurs in Creative MSMEs throughout the Special Region of Yogyakarta shows increasingly competitive market conditions and increasingly limited natural resources so that new breakthroughs are needed to create creative and innovative products. Creative MSMEs often experience delays in their development due to various conventional problems that have not been resolved completely. Strategic efforts are needed to improve the performance and sustainability of Creative MSMEs, including increasing financial literacy so as to increase competitive advantage. This study took samples of Creative MSMEs throughout the Special Region of Yogyakarta, totaling 269 MSMEs throughout the Special Region of Yogyakarta. Data analysis using the Structural Equation Modeling (SEM) model shows that financial literacy is influenced by the latest education of MSME actors, the latest education also influences the competitive advantage of Creative MSMEs in the Special Region of Yogyakarta. But gender does not affect financial literacy and the competitive advantage of Creative MSMEs in the Special Region of Yogyakarta. While financial literacy has an influence on the competitive advantage of Creative MSMEs in the Special Region of Yogyakarta.